Topological confinement by a membrane anchor suppresses phase separation into protein aggregates: Implications for prion diseases - Kalpshree Gogte; Fatemeh Mamashli; Maria Georgina Herrera; Simon Kriegler; Verian Bader; Janine Kamps; Prerna Grover; Roland Winter; Konstanze F. Winklhofer; Jörg Tatzelt (Proceedings of the National Academy of Sciences, 2025)
Protein misfolding and aggregation are a hallmark of various neurodegenerative disorders. However, the underlying mechanisms driving protein misfolding in the cellular context are incompletely understood. Here, we show that the two-dimensional confinement imposed by a membrane anchor stabilizes the native protein conformation and suppresses liquid–liquid phase separation (LLPS) and protein aggregation. Inherited prion diseases in humans and neurodegeneration in transgenic mice are linked to the expression of anchorless prion protein (PrP), suggesting that the C-terminal glycosylphosphatidylinositol (GPI) anchor of native PrP impedes spontaneous formation of neurotoxic and infectious PrP species. Combining unique in vitro and in vivo approaches, we demonstrate that anchoring to membranes prevents LLPS and spontaneous aggregation of PrP. Upon release from the membrane, PrP undergoes a conformational transition to detergent-insoluble aggregates. Our study demonstrates an essential role of the GPI anchor in preventing spontaneous misfolding of PrP C and provides a mechanistic basis for inherited prion diseases associated with anchorless PrP.